1989
DOI: 10.1002/jso.2930410106
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intravesical mitomycin C in the treatment of superficial transitional cell carcinoma of the urinary bladder

Abstract: We treated 47 patients with recurrent transitional cell carcinoma of the bladder with intravesical chemotherapy. Twenty milligrams of mitomycin C per treatment was introduced 7 days after transurethral resection (TUR) or diagnostic cystoscopy, and was repeated at 2-week intervals for five times followed again by cystoscopy. Two more similar courses were administered for a total of 36 weeks. Clinical data revealed no toxicity-related symptoms. Cystoscopic follow-up showed a gradual decline in the presence of tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The selection of drugs currently used for IVC is based on the results observed in clinical trials and series and the lack of toxicity and availability of the drug [ 121. Randomized trials have shown a reduction in recurrence rates in patients receiving adjuvant intravesical pharmacotherapy with BCG [I], doxorubicin [5], mitomycin C [8], or thiotepa [ 131. The drugs most frequently used for IVC are thiotepa, BCG, and MMC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of drugs currently used for IVC is based on the results observed in clinical trials and series and the lack of toxicity and availability of the drug [ 121. Randomized trials have shown a reduction in recurrence rates in patients receiving adjuvant intravesical pharmacotherapy with BCG [I], doxorubicin [5], mitomycin C [8], or thiotepa [ 131. The drugs most frequently used for IVC are thiotepa, BCG, and MMC.…”
Section: Discussionmentioning
confidence: 99%
“…In previous work [8], we summarized our preliminary experience with intravesical MMC administered for a period of 36 weeks. We now report our extended experience to include a 5-year period of follow-up review and treatment of a larger number of patients according to the same protocol.…”
Section: Introductionmentioning
confidence: 99%